(untitled) (Journal Of Educational and Psychological Researches, 2015)
Smart thinking requires a continuous flexible systeroatic teaching in order that the lecturer can reach at easily, The Successful individuals in smart thin king are the most knowledgably with it, where the cognitive (intuitive- systematic) style has common bases with another cognitive styles in many traits, and these two concepts are the core of theorization of the rost important cognitive styles. The present study aims to measure the Smart thinking among university lecturers according to sex variable and recognize the statistically differences significance in the level of cognitive (intuitive- systematic) style among the university lecturers according to sex variable and recognize the correlation between smart thinking and cognitive ( intuitive- Systematic) Style among the university lecturers. The sample consists of two subsamples, the 1st is the sample of building the measures consisting of (80) males and females lecturers and the 2nd is the basic application sample consisting of (150) males and females lecturers , noting that the sample of building the measures differs from the basic application one, where the number of male lecturers is (75) and the female lecturers is (75) and the sample has been selected randomly. The researcher reaches at number of results: The subjects of the sample, according to the comparison between the mean and the hypothetical mean, have smart thinking at the significance level (0,05). 2-The subjects of the sample, according to the comparison between the mean and hypothetical mean, have cognitive (intuitive- Systematic) style at significance level (0,05) 3-There are no statistically significant differences on the measure of smart thinking according to say (male, and females ) variable le at significance level (0,05). 4-There are statistically significant differences on the measure of cognitive (intuitive- systematic) style according to sex (males and females) variable for males at the significance level (0,05). 5-There is a positive correlation be tween smart thinking and cognitive (intuitive- systematic style among university lecturers at significance level (0,05). The researcher reaches at some suggestions and conclusions